The effect of vancomycin powder on bone healing in a rat spinal rhBMP-2 model - Marco C. Mendoza; Kevin A. Sonn; Abhishek Kannan; Sharath Bellary; Sean M. Mitchell; Gurmit Singh; Christian Park; Chawon Yun; Stuart R. Stock; Erin L. Hsu; Wellington K. Hsu (2016)
OBJECTIVE This study aims to quantify the impact of vancomycin powder application on new bone formation and spine fusion rates in a rat posterolateral arthrodesis model. METHODS Thirty-six female Sprague-Dawley rats underwent a posterolateral lumbar spinal fusion (PLF) at the L-4 and L-5 vertebrae. Fusion was elicited via implantation of an absorbable collagen sponge containing 3 µg rhBMP-2. Rats were divided into 3 groups: no vancomycin (control), standard-dose vancomycin, and high-dose vancomycin, based on what was applied to the fusion bed. Clinical studies typically describe the application of 1 g vancomycin into the surgical wound. Presuming an average individual patient weight of 70 kg, a weight-based equivalent dose of vancomycin powder was applied subfascially in the PLF model constituting a "standard-dose" treatment group (14.3 mg/kg, n = 12). To determine whether there is a critical threshold beyond which vancomycin increases the risk of pseudarthrosis, a 10-fold higher dose was administered to a "high-dose" treatment group (143 mg/kg, n = 12). No vancomycin powder was applied to the surgical site in the control group (n = 12). Fusion was evaluated with plain radiographs at 4 and 8 weeks after surgery. The spines were harvested after the 8-week radiographs were obtained and evaluated using manual palpation, microCT analysis, and histological analysis. RESULTS Radiographs demonstrated equivalent bridging bone formation in all groups. No significant differences in fusion scores were seen in the standard-dose (mean 2.25) or high-dose (2.13) treatment groups relative to untreated control animals (1.78). Similarly, fusion rates did not differ significantly different between vancomycin-treated animals (100% for both groups) and control animals (92%). Quantification of new bone formation via microCT imaging revealed no significant between-groups differences in the volume of newly regenerated bone (control vs standard-dose vancomycin, p = 0.57; control vs high-dose vancomycin, p = 0.53). CONCLUSIONS This is the first in vivo study to specifically address the development of pseudarthrosis after intrawound application of vancomycin during fusion surgery. Our results demonstrate that vancomycin powder does not inhibit fusion rates at a dose that is the weight-percentage equivalent of what is routinely used by surgeons. Moreover, bone formation and fusion rates were not reduced even after administration of a vancomycin dose that is 10-fold higher than that which is typically administered clinically. Our findings suggest that if there is a critical threshold above which vancomycin inhibits bone healing, such a dose is out of the range which might be considered reasonable for clinical use.